São José dos Quatro Marcos and the Installation of Duque de Caxias Mixed Rural School (1966-1972) (Research, Society and Development, 2021)
This work aims to bring to light the initial movement of farmers and their families to create a school in São José dos Quatro Marcos - MT for the schooling of their children, as well as the way in which it was organized by their first teachers. The research has as methodological theoretical referential the perspective of Cultural History (Chartier, 1991) and School Institutions (Sanfelice, 2007). To this end, we used documents found in the Public Archives of Cáceres, such as periodicals and contracts, research about recent colonization and memorial works. The temporal delimitation (1966-1972) is justified by the creation of Duque de Caxias Mixed School and the period in which the teachers Inivaldo Mila and Maria Luiza were in charge of the school. It was concluded that in, that reality, the school became a priority to guarantee the permanence in areas of recent colonization, because, without offering school education to the children of the immigrants, the families would not remain in their lands. Therefore, they spared no effort to build it in the middle of the forest.